Effect of side chain hydrophobicity and cationic charge on antimicrobial activity and cytotoxicity of helical peptoids. Issue 2 (15th January 2018) - Lee, Jiyoun; Kang, Dahyun; Choi, Jieun; Huang, Wei; Wadman, Mayken; Barron, Annelise E.; Seo, Jiwon
Graphical abstract: Abstract: Peptoids are peptidomimetic polymers that are resistant to proteolysis and less prone to immune responses; thus, they can provide a practical alternative to peptides. Among the various therapeutic applications that have been explored, cationic amphipathic peptoids have demonstrated broad-spectrum antibacterial activity, including activity towards drug-resistant bacterial strains. While their potency and activity spectrum can be manipulated by sequence variations, bacterial selectivity and systemic toxicity need to be improved for further clinical development. To this aim, we incorporated various hydrophobic or cationic residues to improve the selectivity of the previously developed antibacterial peptoid1 . The analogs with hydrophobic residues demonstrated non-specific cytotoxicity, while those with an additional cationic residue showed improved selectivity and comparable antibacterial activity. Specifically, compared to1, peptoid7 showed much lower hemolysis and cytotoxicity, while maintaining the antibacterial activity. Therefore, we believe that peptoid7  has the potential to serve as a promising alternative to current antimicrobial therapies.